Control of shaping and thermal resistance of metakaolin-based geopolymers. (15th February 2017) - Sabbatini, A.; Vidal, L.; Pettinari, C.; Sobrados, I.; Rossignol, S.
Abstract: This paper presents results from experimental studies on the thermal resistance and dilatometry analysis of various geopolymer formulations, which were prepared by mixing alkaline solutions, metakaolin and reinforcements. Nine compositions were tested by dilatometric analysis and thermal resistance at high temperature (800 °C). Structural and microstructural analysis was conducted to verify the geopolymerization, and differential thermogravimetric analysis was performed to evaluate the nature of water, depending on the formulation. Some key parameters were identified as critical parameters that influenced the geopolymer properties, such as the nature (Na or K) and the molar concentration of the alkaline cation ([M] < 16 mol/L), the molar concentration of silicon ([Si] < 39 mol/L) and the alkaline metal to aluminum ratio (M/Al < 0.65). Finally, it was possible to arrange the various formulations in a ternary scheme as functions of the metal, aluminum and silicon concentrations. This scheme may represent a roadmap for controlling the thermal resistance of geopolymer materials. Graphical abstract: Highlights: The alkaline cation nature and amount control the shrinkage values at room temperature. Shaping of geopolymers in complex geometries is possible. The chemical composition of geopolymer induces three behaviors after heating. M/Al ratio (M = Na, K) controls fire resistance of geopolymers at high temperature.